1950
DOI: 10.1111/j.1749-6632.1950.tb39902.x
|View full text |Cite
|
Sign up to set email alerts
|

The Role Played by Leucocytes and Platelets in Anaphylactic and Peptone Shock

Abstract: If one goes back to the earlier theories of anaphylaxis, the number of separate points of view, or schools, defending entirely independent ideas on the mechanism of this important phenomenon becomes quite impressive. We might distinguish among the different conceptions-the immunological, the hematological, and the physiological or pharmacological-according to the main principles involved and the personal interests and scientific outlook of their proponents. Today, it is rather trivial to say that the liberatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

1956
1956
1978
1978

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…Glycogen and certain other polysaccharides have been shown to cause leucopenia and thrombocytopenia in the rabbit (Rocha e Silva, 1950). Such effects could also be obtained when cellulose sulphate 25 mg/kg was given to this species (Rothschild, 1968); however, neither leucopenia nor loss of circulatory platelets were observed in rats treated with cellulose sulphate at concentrations causing maximal kininogen breakdown.…”
Section: Discussionmentioning
confidence: 99%
“…Glycogen and certain other polysaccharides have been shown to cause leucopenia and thrombocytopenia in the rabbit (Rocha e Silva, 1950). Such effects could also be obtained when cellulose sulphate 25 mg/kg was given to this species (Rothschild, 1968); however, neither leucopenia nor loss of circulatory platelets were observed in rats treated with cellulose sulphate at concentrations causing maximal kininogen breakdown.…”
Section: Discussionmentioning
confidence: 99%
“…Rocha e Silva (1950) found that the perfused liver of the sensitized dog released only traces of histamine, when challenged by the antigen, unless the perfusion fluid consisted of whole blood without an anticoagulant.…”
Section: Discussionmentioning
confidence: 99%
“…The possible effect of residual blood on histamine values was also tested in the following way. Each of two rabbits received an intravenous injection of glycogen in a dose which produced a rapid lowering of blood histamine concentration (Rocha e Silva, 1950;. At the time of killing the animals, 10 min after glycogen injection, the blood histamine had fallen to 14% of that before glycogen.…”
Section: Collection Of Blood Samplesmentioning
confidence: 99%